2014
DOI: 10.1002/jbm.b.33182
|View full text |Cite
|
Sign up to set email alerts
|

History and performance of implant materials applied as peritendinous antiadhesives

Abstract: Peritendinous fibrotic adhesions after tendon surgery are still a problem up-to-date. Approaches to overcome or at least minimize adhesion formation include implantation of barrier materials, application of lubricants or combinations of materials and functionalized drugs that are controllably released and support the healing tendon to glide and achieve the full range of motion after regeneration. Although a huge amount of different materials have been experimentally tested, the optimal strategy with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 145 publications
0
21
0
Order By: Relevance
“…Since Thomas et al first reported the efficacy of HA in preventing postoperative adhesions in a rabbit flexor tendon model [25], it has become one of the most widely used peritendinous anti-adhesives [26]. The scientific rationale for the use of HA in the prevention of adhesion formation is based on several biological effects, including non-coagulant activity, modulation of fibrous tissue formation, barrier effect to fibrinogen and inhibition of superoxide release from granulocytes [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since Thomas et al first reported the efficacy of HA in preventing postoperative adhesions in a rabbit flexor tendon model [25], it has become one of the most widely used peritendinous anti-adhesives [26]. The scientific rationale for the use of HA in the prevention of adhesion formation is based on several biological effects, including non-coagulant activity, modulation of fibrous tissue formation, barrier effect to fibrinogen and inhibition of superoxide release from granulocytes [27].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to tendon adhesions, the barriers used to prevent them must also promote gliding to avoid interfering with tendon movement [95]. To this end, hyaluronic acid gels seem to be the most promising option, although positive results have been mostly observed in preclinical studies since the clinical findings have produced limited and moderate results [53,96]. One example of a commercially available product based on hyaluronic acid is Hyaloglide®, a highly purified auto-cross-linked hyaluronic acid gel.…”
Section: Mechanical Barriersmentioning
confidence: 99%
“…Currently, the main fibrinolytic agents investigated are streptokinase, t-PA and PAI-1. Nevertheless, the results obtained have shown poor performance in animal studies and side effects such as bleeding after their use [3,78,96,105].…”
Section: Antiadhesive Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An insufficiently strong scar tissue lacking the aligned collagen organization seen in normal healthy tendons often leads to reruptures. The second drawback, adhesion formation between the regenerating tendon and the surrounding tissue, occurs in 7–15% of all cases, leading to a reduced range of motion, which ends up in higher work disability and costs . To address these two problems, an elastic biodegradable polymer tube was developed in our research team .…”
mentioning
confidence: 99%